How Philosophical is Informal Logic? - John Woods (Informal Logic, 2000)
Consider the proposition, "Informal logic is a subdiscipline of philosophy". The best chance of showing this to be true is showing that informal logic is part of logic, which in turn is a part of philosophy. Part 1 is given over to the task of sorting out these connections. If successful, informal logic can indeed be seen as part of philosophy; but there is no question of an exclusive relationship. Part 2 is a critical appraisal of the suggestion that informal logic is applied epistemology. Part 3 examines the claim that informal logic has failed to penetrate into mainstream philosophy, and suggestions for amelioration are considered.